CONTRIBUTION TO THE DEFENSE FUND BY SCHOOLS OF KHORAZM REGION - Allaberganov Sherali Yuldashevich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides information about clothing, food, and money collected by residents of the republic, employees of the education system, and schoolchildren, to war-ravaged territories, to the front, and to create a defense fund. Since the beginning of the war in June 1941, the population that had not gone to the front was struggling with all their might, they worked diligently, providing food, clothing and housing to evacuated residents of the entire Soviet Union. Thanks to this, our people have become an example for the peoples of the whole world with their tolerance and hospitality.